PENGARUH POTENSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DAN KAPASITAS FISKAL DI KABUPATEN/KOTA DI JAWA BARAT - LISNA LISNAWATI (Universitas Widyatama, 2018)
This study aims to analyze the effect of Regional Tax Potential on Regional Original Revenue and Fiscal Capacity in Districts / Cities in West Java in 2012 to 2016. The data used in this study was obtained from the Local Tax Target Report, Budget Realization Report and Fiscal Capacity Index (IKF ) from 2012 to 2016 issued by the Directorate General of Financial Balance (DGT) of the Ministry of Finance of the Republic of Indonesia. The research method used in this study is a descriptive research method that uses a quantitative analysis approach. The purpose of this descriptive research is to make a description of the facts, nature, relationships, and influences between the phenomena investigated. The research instrument used is Simple Regression, which is one method of bivariate analysis. The results of the study and hypothesis testing showed that the Potential of Local Taxes had a significant effect on Regional Original Revenue and that the Potential of Regional Taxes did not significantly influence Fiscal Capacity.